THE POLITENESS STRATEGIES USED BY RON CLARK IN THE RON CLARK STORY MOVIE - AFIDHA, ZAIZIN MIFTAKHUL (Jurnal Ilmiah Mahasiswa FIB, 2015)
People use language to communicate with others. To  make the communication run well a politeness strategy is needed. This research presents the politeness strategies expressed by Ron Clark  in The Ron Clark Story movie. The Ron Clark Story is a movie about the experience of a teacher in New York City. The teacher, Ron Clark, inspires the underachieving children to have a big dream and to attain their goals. The politeness strategies used by Mr. Clark is  interesting to be  analyzed. There are two problems to be solved the study, namely: 1) What politeness strategies are used by Mr. Clark in The Ron Clark Story Movie?; and 2) Which politeness strategies are mostly used by Mr. Clark in The Ron Clark Story Movie? Thus, it aims to discuss the type of politeness strategies and find out politeness strategies which are mostly used by the main character.  The  researcher  used  qualitative approach to conduct this research.  This research used document analysis since it analyzed Mr. Clark’s conversation in The Ron Clark Story  movie.  The data of this  research are Mr. Clark’s  utterances containing politeness strategies  which were  taken from  The Ron Clark Story movie. Brown and Levinson’s theory is used to analyze the utterances.  The result of the  research  showed that four strategies are applied in the dialogue  those are bald on record  strategy, positive politeness strategy, negative politeness strategy, and off record. It is found that Mr. Clark mostly used positive politeness strategy when he met others because he wanted  to be closer and he wanted to minimize the different social status with his interlocutor.  Based on the results, the  researcher  suggests to the next researchers to conduct research on politeness strategies in the other form of movie to expand the study. Besides, the next researcher can use not only Brown and Levinson theory but also other theories of politeness strategies.